Family social capital on public respond to COVID-19 in Indonesia - Supriyati Supriyati; kun Habibah; Ade Wahyuni; Rafif Adianto Abdul Wahab; Kenji Sebastian Halim; Erdananda Aditya Nugroho; Mohamad Sofyan Soddiq (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Background: The Coronavirus Disease 2019 (COVID-19) gave impact on the various sectors, not limited to the health sector. In the other hand, social capital was help Indonesian community from the 1998 crisis. This study was aimed to describe the family social capital on COVID-19 prevention and examine factors contribute to family social capital among Indonesia citizen.Method: Cross-sectional data was derived from community survey conducted in Indonesia (February, 2021). A number of 581 Indonesian citizen aged 18 – 59 years old had participated in this study. Data was collected by using online questionnaire that distributed through social media. Furthermore, univariate, bivariate, and multivariate analysis were carried out in this study.Result: Most of respondent (55%) had high family social capital. The family social capital include (1) education function, (2) protective function, and (3) reinforcement function. They were discussed with their family member about the hazard of COVID-19, health protocol as strategy for COVID-19 prevention, and tried to remind each other to apply health protocol in the daily activities. Furthermore, their family were provide face mask and hand sanitizer for family member as a tool of COVID-19 prevention. Family was the second highest information source (65%) regarding Covid-19 and prevention among family member. In addition, there was a significant association between perception toward health protocol (p = 0.000), vulnerable status (p = 0.044), and economic status (p = 0.000), and family social capital. Community empowerment in the COVID-19 prevention through family social capital was challenging. Conclusion: This study demonstrated that Indonesian community had high family social capital. Moreover, public health expert need to empower family social capital in the COVID-19 prevention.